Does managerial myopia hinder green technological innovations? an examination based on Chinese-listed heavy polluters - Li, Ziwei; Wu, Yuan (Frontiers in Environmental Science, 2023)
Under the guidance of a high-quality development strategy, upholding the long-term concept of green development is the foundation allowing polluting companies to resist external environmental threats and retain their legitimate business statuses. However, the top managers of companies do not always hold long-term perspectives. To this end, we investigate the impact of management myopia on green technological innovation and its mechanism of action for heavy polluters using zero-inflated Poisson regression analysis for 2007-2020 for A-share listed heavy polluters. The empirical results show that green technological innovation decreases 1.251 times for each 1-unit increase in the management myopia level demonstrated by heavily polluting enterprises. Moreover, these results are more significant in heavily polluting enterprises with high management shareholding and those that receive more government subsidies. However, managerial myopia is suppressed in heavily polluting firms with many independent directors and institutional investors. A further study found that managerial myopia had the most significant negative impact on green technological innovation for heavy polluters in the central region, and each 1-unit increase in the managerial myopia level decreased the firm's green technology innovation level by 3.577 times. The findings of this paper have important implications for heavily polluting firms seeking to improve their senior management appointments and governance structures, promote green technology and technological innovation, and achieve high-quality corporate development.